Study on the impact of roller convexity excursion of high-speed cylindrical roller bearing on roller's dynamic characteristics. (September 2016) - Zhang, Wenhu; Deng, Sier; Chen, Guoding; Cui, Yongcun
Abstract: This paper presents dynamics differential equations of high-speed cylindrical roller bearing considering the impact of roller convexity excursion on mass center of roller, which are solved by GSTIFF (Gear Stiff) integer algorithm with variable step. The impact of roller convexity excursion on roller's dynamic characteristics is investigated theoretically, and the accuracy of dynamic model of high-speed cylindrical roller bearing and the computation results are demonstrated via Caba3D. The findings are as following: 1) Roller convexity excursion has tiny impact on tilting angle of roller but great impact on skewing angle, and the bigger convexity excursion the bigger skewing angle; 2) For PCRC(partially crowned roller with the center of crowned profile locating at the center line of roller), PCRE(partially crowned roller with the center of crowned profile locating at the ends of roller), fully crowned roller and logarithmic crowned roller, the amounts of roller convexity excursion are less than 0.6 mm, 0.4 mm, 0.4 mm and 0.4 mm, respectively; 3) The sensitivity to roller convexity excursion for four types of rollers is different, and the sensitivity level of roller from small to large is logarithmic crowned roller, PCRE, PCRC, fully crowned roller. 4) Among four types of crowned rollers, anti-speed capability and anti-load capability of logarithmic crowned roller are the most excellent, followed by PCRE and PCRC, and fully crowned roller is the worst one in both aspects. Highlights: An improved slice method is applied to the handling of contact issue between roller and raceways. Roller convexity excursion impact on roller's dynamic characteristics and distribution of contact stress are studied. The dynamics differential equations considering the impact of roller convexity excursion on mass center of roller is presented. Some conclusions for the designing and machining process of roller's convexity for high speed roller are acquired.